2017
DOI: 10.1016/j.cgh.2016.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Similar Risk of Cardiopulmonary Adverse Events Between Propofol and Traditional Anesthesia for Gastrointestinal Endoscopy: A Systematic Review and Meta-analysis

Abstract: Propofol sedation has a similar risk of cardiopulmonary adverse events compared with traditional agents for gastrointestinal endoscopic procedures. Propofol use in simple endoscopic procedures was associated with a decreased number of complications. When used for gastrointestinal endoscopic procedures of a complex nature and longer duration, propofol was not associated with increased rates of hypoxemia, hypotension, or arrhythmias. Administration of propofol by gastroenterologists does not appear to increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
92
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 63 publications
2
92
0
6
Order By: Relevance
“…Advanced endoscopic procedures are highly effective under propofol sedation, with completion rates very nearly reaching 100% 26 27. Moreover, the use of propofol in endoscopy has been reported as safe in a recent meta-analysis of over 2500 patients 28. Similar rates of cardiopulmonary adverse events were reported in those receiving propofol when compared with traditional sedation.…”
Section: Discussionmentioning
confidence: 82%
“…Advanced endoscopic procedures are highly effective under propofol sedation, with completion rates very nearly reaching 100% 26 27. Moreover, the use of propofol in endoscopy has been reported as safe in a recent meta-analysis of over 2500 patients 28. Similar rates of cardiopulmonary adverse events were reported in those receiving propofol when compared with traditional sedation.…”
Section: Discussionmentioning
confidence: 82%
“…Although the study of Wadhwa et al [4] is intriguing, the broader applicability of their conclusions to pleuroscopy may be limited. A study by Chhajed et al [21] demonstrated that pleuroscopy, performed under moderate sedation with midazolam, hydrocodone, and pethidine, was associated with significant hypoventilation (mean change in PcCO 2 from a baseline of 13.2 ± 5.3 mm Hg).…”
Section: Discussionmentioning
confidence: 92%
“…No studies have directly compared MAC with propofol-based sedation administered by nonanesthesiologists. Wadhwa et al [4] performed a meta-analysis to compare the risks of propofol versus traditional anesthesia for gastrointestinal endoscopy. In a subgroup of 23 studies, MAC was noninferior for causing cardiopulmonary complications compared with propofol-based sedation administered by gastroenterologists (OR, 0.82; 95% CI, 0.55-1.21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple meta-analyses have shown no increased risk of CPEs with propofol usage and possibly shorter recovery times. [218][219][220][221] The decision to proceed with general anesthesia should be made by the endoscopists and anesthesia team and be individualized based on patient morbidity and complexity of the underlying procedure. Generally in cases of duodenal/gastric outlet obstruction, gastric stasis, or anticipated long procedure times, general anesthesia with endotracheal intubation may be wise to prevent aspiration.…”
Section: Risk Reductionmentioning
confidence: 99%